One Stop Shops for Public Services: Evidence from Citizen Service Centers in Brazil. (13th September 2020) - Fredriksson, Anders
Abstract: Citizen Service Centers are government offices where different authorities are co‐located and where several public services are offered in the same physical location. The goal of implementing such One Stop Shops for public services is to solve problems with a malfunctioning government bureaucracy for frontline service delivery. In spite of reforms in at least 70 countries, however, there are few evaluations. This paper evaluates the impact of Poupatempo ("Savetime"), a Brazilian Citizen Service Center reform that has inspired similar programs in other countries. We collect data on one of the most common errands at the Brazilian bureaucracy, driver's license renewal, and evaluate the impact of Poupatempo on the time, number of trips, and payments needed to undertake the renewal, and on other variables representing transaction costs, red tape, and transparency in the citizen‐state interaction. Our difference‐in‐differences estimates indicate large reductions in the time expended by citizens and in proxies for transaction costs, but are less encouraging for the social quality of the licensing procedure, which we also evaluate. We discuss whether incentives to speed up processes prevailed where other steering instruments would have been more appropriate, and explore remedies. We also discuss limitations to establishing a true One Stop Shop.